Research Response On “Pediatric”: A Scientometric Study On The Literature Output From Wos - S, Abirami; R, Senthilkumar (Kongunadu Research Journal, 2019)
The hit rate of publications even more grew on the basis of everyday development in each and every department. To study the growth and publication trend in “PEDIATRIC” decided to use scientometric tools.The desired data were downloaded from web of science (WOS) on pediatric. The analysis was based on the year wise growth on publications, publications based on languages, document wise publications and top ten journals; the Lotka’s Law has been analyzed. The scope and hypothesis are framed for the present study. The research topic was “Research Response on “Pediatric”: A Scientometric Study on the Literature Output from WOS”.